Implementation of Government Policies in Handling Covid 19 in Ogan Komering Ilir (OKI) Regency - Alam, M. Ilyas Panji; Suatmiati, Sri; Hayatuddin, Khalisah (Technium Social Sciences Journal, 2022)
COVID-19 is a global pandemic that certainly raises concerns for various groups, especially among the community. Since being designated by WHO as a global pandemic, the management of handling COVID-19 has become a challenge for countries with limited resources and health care systems. This study aims to study the positive laws governing the handling of covid 19 and the implementation of the policies of the Ogan Komering Ilir (OKI) district government. The data used in this research is secondary data, which consists of basic law and secondary legal material which is the result of relevant legal research in the form of journals, books, and scientific works on the internet. Literature study is used as a technique to obtain data, which is then processed by descriptive analysis which is a method to get conclusions. The results showed that the implementation of government policies in handling covid 19 in Ogan Komering Ilir Regency had been responded to and carried out well through the issuance ofRegulation of the Regent of Ogan Komering Ilir Regency No. 39 Year 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort for Prevention and Control of Corona Virus Disease 19 in Ogan Komering Ilir Regency and Ogan Komering Ilir Regent Regulation Number 63 of 2020 concerning Adaptation of New Habits Towards a Productive and Safe Society in the Situation of Corona Virus Disease 2019 (Covid- 19